INTERPRETASI KEPERCAYAAN DEBITUR KKM CENTRAL SANTOSA FINANCE CABANG SURABAYA - Izaak, Wilma Cordelia; Rini, Hesty Prima (BISMA: Jurnal Bisnis dan Manajemen, 2019)
The purpose of this study is to analyze and interpret the effect of perceived quality and perceived value on consumer satisfaction and loyalty. The research sample was taken using a purposive sampling technique with the sample consisting of 67 debtors of motorbike ownership credit at the Central Santosa Finance Surabaya. The research data were analyzed using Partial Least Square (PLS) method. The results showed that perceived quality had a significant positive effect on loyalty through satisfaction, and perceived value had a significant positive effect on loyalty, both directly and indirectly through satisfaction. However, perceived quality did not have a direct effect on loyalty. These results implied that the company should continuously improve its service quality to maintain customer trust, satisfaction, and loyalty. Keywords: loyalty, perceived quality, perceived value, satisfaction.